(untitled) (Kerala Journal of Psychiatry, 2019)
Background: Clozapine is widely used for the treatment of resistant Schizophrenia (Sz). Metabolic syndrome (MetS) is its recognized side effect. Reports on the side effects of Clozapine are scanty from Kerala. Hence a prospective observational study was conducted. Aim: The aim of the present study was to find the incidence of Metabolic syndrome in patients with psychosis, after 12 weeks of treatment with clozapine in a tertiary care centre in Kerala. Methods: Patients diagnosed as Schizophrenia or Delusional disorder based on International Classification of Diseases (ICD)-10 and not meeting the threshold criteria for MetS according to the National Cholesterol Education Program Adult Treatment Panel III (NCEP ATP III), and on Clozapine treatment were recruited and followed up for at least 12 weeks. Augmentation, when needed, was limited to Amisulpride, Aripiprazole, and/or Modified Electroconvulsive Therapy (MECT). Bodyweight, waist circumference, blood pressure, fasting blood sugar, and triglycerides levels were measured at the enrolment and after 12 weeks. Seventy-five patients completing follow up for 12 weeks were considered as study subjects. Patients who fulfilled NCEP ATP III criteria at 12 weeks were diagnosed as having MetS. Results: Study sample of 75 had not met the threshold criteria of NCEP ATP III based MetS diagnosis at the study entry. But among them, 23 met no criteria, 23 met one criterion and 29 met two criteria. Out of 75 patients, 32 (42.7%) developed Metabolic Syndrome at three months. Among 23 who met no criteria at intake, 3 (13%) developed MetS, while it was 9 (39%) in 23 who met 1 criterion and 20 (69%) in 29 who met 2 criteria. The mean Clozapine dose at discharge was 514Â±148 mg in those who developed MetS while it was 428Â±164 mg in those who did not. This difference was statistically significant (p<0.05). Conclusion: Incidence of MetS is high in Clozapine receiving Psychotic patients. The present study showed that in the study population, risk factors have a cumulative effect on the development of this side effect, and the risk is high when the dose of clozapine is higher.